2018
DOI: 10.5005/jp-journals-10024-2247
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Salivary Catalase, α-Amylase, and Cotinine Levels in Chronic Smokers: A Comparative Study

Abstract: Introduction:One of the common practices observed in many parts of the world is smoking, of which tobacco forms an important constituent which is burned and inhaled. Smoking is known to have potential effect on body's immune system, antioxidants level, and salivary cotinine levels. Hence, we planned the present study to evaluate the impact of cigarette smoke on salivary antioxidant levels and cotinine levels in smokers and nonsmokers. Materials and methods:The present study included assessment of salivary para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…A case-control study among tobacco chewers showed a significant increase and decrease in the salivary MDA and CAT levels compared to controls. [41] These results are in consistency with results of our study which also showed a significant increase and decrease in the salivary MDA and CAT levels among tobacco chewers.…”
Section: Discussionsupporting
confidence: 92%
“…A case-control study among tobacco chewers showed a significant increase and decrease in the salivary MDA and CAT levels compared to controls. [41] These results are in consistency with results of our study which also showed a significant increase and decrease in the salivary MDA and CAT levels among tobacco chewers.…”
Section: Discussionsupporting
confidence: 92%
“…[ 25 ] A case–control study among tobacco chewers showed a significant increase and decrease in the salivary MDA and CAT levels compared to controls. [ 26 ] These results are found to be similar to the results of the present study. In contrast, a previous study among 200 smokers and nonsmokers showed no significant difference in salivary CAT levels.…”
Section: Discussionsupporting
confidence: 92%
“…A large panel of papers evaluating the antioxidant capacity of smokers' saliva is available. The results of most studies clearly indicate that smoking cigarettes is accompanied by decreased activity of endogenous salivary enzymatic antioxidants such as SOD, CAT and Px as well as reduced concentration of non-enzymatic endo-and exoantioxidants: GSH, UA (Nagler) and vitamin C (Klein et al, 2003;Reznick et al, 2003;Nagler, 2007;Abdolsamadi et al, 2011;Falsafi et al, 2016;Arbabi-Kalati et al, 2017;Singh et al, 2018). According to the available evidence, cigarette smoke disturbs the metabolism of trace elements which are cofactors of antioxidant enzymes (copper and zinc as cofactors of SOD, iron as cofactor of CAT), thus reducing their activity (Nobari et al, 2021).…”
Section: Cigarette Addiction and Oral Healthmentioning
confidence: 99%